2010
DOI: 10.1017/s0265051710000082
|View full text |Cite
|
Sign up to set email alerts
|

‘Workplace landscapes’ and the construction of performance teachers' identity: the case of advanced music training institutions in Greece

Abstract: This paper draws on the metaphor of 'workplace landscape' to highlight the role of institutional values, evidenced within a Greek University Music Department and a MusicConservatoire, in the construction of musical performance teachers' professional identity. Underpinned by a social constructionist framework and within an ethnographic case study approach, the findings revealed that, on the one hand, participating teachers were constrained by the 'cultural scripts' within their workplaces, and on the other, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Purser reported that although the teachers had been able to develop their work with reference to their own conservatoire teachers, alongside experience and reflection, these were ‘people working in professional isolation’ with limited opportunities to ‘exchange information (or knowledge, or wisdom)’. Triantafyllaki (2010: 197) reinforces this view, arguing that institutions should provide studio teachers with ‘the space, time and resources to explore and reflect on their professional practice as it develops both within and beyond their educational workplace’. Although Purser (2005: 298) concedes that peer observation schemes are becoming more common in conservatoires, he notes that students’ performance achievements remain more visible than studio practices, and although he would not want to homogenise those practices ‘it is hard not to draw the conclusion that some forum for sharing experience and modes of good teaching practice would be beneficial’.…”
Section: Pedagogical Implications Of Isolationmentioning
confidence: 99%
See 3 more Smart Citations
“…Purser reported that although the teachers had been able to develop their work with reference to their own conservatoire teachers, alongside experience and reflection, these were ‘people working in professional isolation’ with limited opportunities to ‘exchange information (or knowledge, or wisdom)’. Triantafyllaki (2010: 197) reinforces this view, arguing that institutions should provide studio teachers with ‘the space, time and resources to explore and reflect on their professional practice as it develops both within and beyond their educational workplace’. Although Purser (2005: 298) concedes that peer observation schemes are becoming more common in conservatoires, he notes that students’ performance achievements remain more visible than studio practices, and although he would not want to homogenise those practices ‘it is hard not to draw the conclusion that some forum for sharing experience and modes of good teaching practice would be beneficial’.…”
Section: Pedagogical Implications Of Isolationmentioning
confidence: 99%
“…Thus, Kingsbury (1988: 34) notes that the administrative offices of an American conservatory are magnificently furnished in ‘shining evidence of a tradition of elegance’, and he describes the concert hall as a splendid focal point, with ‘an arched parquet ceiling and an expansive, handsome wooden concert stage’. Similarly, Triantafyllaki (2010: 191) describes the concert hall of a Greek conservatoire with its ‘imposing, high, glass ceiling and solid stone columns’, representing the public front of the institution and making students’ performing activity highly visible.…”
Section: Cultural Implications Of Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…There are studies showing that the identity the teacher brings to his lessons and his degree of professional specialisation influence the way the teacher approaches his students (Kennel, 2002; Triantafyllaki, 2010). The positions of teacher and student seem however in many ways institutionally regulated and thus shaped by the culture of the institution in which the activity takes place.…”
Section: Introductionmentioning
confidence: 99%